Cancer/testis antigens: novel tools for discerning aggressive and non-aggressive prostate cancer - Shiraishi, Takumi (Nature Publishing Group, 2012)
The introduction of serum prostate-specific antigen (PSA) in the 1980s has dramatically altered and benefited the initial diagnosis of prostate cancer. However, the widespread use of PSA testing has resulted in overdetection and overtreatment of potentially indolent disease. Thus, a clinical dilemma today in the management of prostate cancer is to discern men with aggressive disease who need definitive treatment from men whose disease are not lethal. Although several serum and tissue biomarkers have been evaluated during the past decade, improved markers are still needed to enhance the accuracy, with which patients at risk can be discerned and treated more aggressively. The cancer/testis antigens (CTAs) are a group of proteins that are restricted to the testis in the normal adult, but are aberrantly expressed in several types of cancers. Because of their restricted expression pattern, the CTAs represent attractive biomarker candidates for cancer diagnosis/prognosis. Furthermore, several studies to date have reported the differential expression of CTAs in prostate cancer. Here, we review recent developments that demonstrate the potential of the CTAs as biomarkers to discern the aggressive phenotype of prostate cancer.